Pemberdayaan Perempuan Melalui Pelatihan Wirausaha Bagi Perempuan Desa Matang Peulawi Kecamatan Peureulak Kabupaten Aceh Timur - Ismuhadi; Huda, Muhammad (PASAI : Jurnal Pengabdian kepada Masyarakat, 2024)
This study aims to evaluate the impact of entrepreneurship training on the empowerment of women in Matang Peulawi Village, Peureulak Subdistrict, East Aceh Regency. The research method used is descriptive qualitative with a case study approach. Data were collected through in-depth interviews, observations, and documentation of the training participants. The results of the study indicate that entrepreneurship training has enhanced the business knowledge and skills of the women, as well as strengthened their confidence and economic independence. The participants were able to start and manage small businesses independently, which had a positive impact on the welfare of their families and the local community. The study concludes that entrepreneurship training is an effective strategy for empowering women in rural areas.